2012
DOI: 10.1590/s0102-67202012000200011
|View full text |Cite
|
Sign up to set email alerts
|

Correlação da infiltração das células Natural Killer (NK) CD 57+ no prognóstico do adenocarcinoma gástrico

Abstract: DESCRITORES ABCDDV/854ABSTRACT -Background -To evaluate the concentration of Natural Killer cells (NK) cells in adenocarcinoma of the stomach, and its correlation with prognostic factors and survival. Methods -Seventy-two patients with gastric adenocarcinoma who underwent gastric resection surgery and D2 lymphadenectomy in the period 1997-2007 were analyzed. The concentration of NK cells was evaluated by immunohistochemistry technique with the reagent CD57. Patients were divided into two groups: high concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The data show that NK cells exhibit cytotoxic activity against allogeneic and autologous cancer cell lines, including gastric cancer cells lines[ 147 ], and could prevent tumor metastatic spreading[ 148 , 149 ]; additionally, intra-tumor infiltration of NK cells is associated with a longer survival in neoplastic patients[ 150 ]. Patients with advanced gastric adenocarcinoma having a high density of NK cells demonstrated a prolonged survival rate vs those with the low density NK[ 151 ]. The number of apoptotic NK cells (Fas + NK cells) is significantly higher in gastric neoplasia patients vs normal controls and is correlated to the tumor progression[ 152 ].…”
Section: Current Immunotherapeutic Strategies In Gastric Cancermentioning
confidence: 99%
“…The data show that NK cells exhibit cytotoxic activity against allogeneic and autologous cancer cell lines, including gastric cancer cells lines[ 147 ], and could prevent tumor metastatic spreading[ 148 , 149 ]; additionally, intra-tumor infiltration of NK cells is associated with a longer survival in neoplastic patients[ 150 ]. Patients with advanced gastric adenocarcinoma having a high density of NK cells demonstrated a prolonged survival rate vs those with the low density NK[ 151 ]. The number of apoptotic NK cells (Fas + NK cells) is significantly higher in gastric neoplasia patients vs normal controls and is correlated to the tumor progression[ 152 ].…”
Section: Current Immunotherapeutic Strategies In Gastric Cancermentioning
confidence: 99%
“…The prognosis of the GC is significantly correlated with the tumor-associated immune cells in tumor immune microenvironment [2]. Tumor-associated immune cells such as natural killer (NK) cells, dendritic (DC) cells, helper T1 (Th1) cells, and cytotoxic CD8 cells in the tumor microenvironment are generally correlated with favorable outcome [36]. In contrast, infiltration of B cells, regulatory T (Tregs) cells, and Th2 and Th17 cells promotes tumor development and correlates with a poor prognosis [79].…”
Section: Introductionmentioning
confidence: 99%
“…It was recently reported that tumor-infiltrating NK cells were decreased in human GC; moreover, the production of IFNγ and TNFα by these cells was impaired by tumor-associated monocytes/macrophages via TGFβ1 36 . In contrast, patients with GC had a better survival when they presented higher concentrations of NK cells, an effect that was more evident in advanced stage cases 37 . Our work associates the risk to develop GC with the B KIR genotypes and the gene cluster included within the telomeric part.…”
Section: Discussionmentioning
confidence: 88%